Distance travelled for brain tumour surgery: A Low- and Middle-income Country Perspective - Mohammad Hamza Bajwa; Mashal Murad Shah; Muhammad Usman Khalid; Ahsan Ali Khan; Nida Zahid; Saad bin Anis; Naveed Zaman Akhunzada; Altaf Ali Laghari; Muhammad Faraz Raghib; Sameen Siddiqi; Syed Ather Enam (Journal of the Pakistan Medical Association, 2022)
Objective: To examine the effect of distance travelled for brain tumour surgery on patient outcomes in an LMIC. Methods: Data were collected as part of the Pakistan Brain Tumour Epidemiology Study (PBTES) for brain tumour patients who underwent surgery in 2019. Mapping software was used to calculate the distance travelled by each patient from their primary address to the hospital. This was analysed in correlation with outcomes (change in KPS score, current status) and demographic variables. Results: Of 2366 patients, the median distance travelled across the country was 104 km (IQR: 9.07 - 304). Only 970 (41%) patients had access to brain tumour surgical care within 50 km of their primary address. A total of 372 (15.7%) patients requiring brain tumour surgery had to travel more than 500 km to reach their primary care hospital. Patients travelling more than 50 km for brain tumour surgery had better pre- and post-surgery Karnofsky performance scores (p<0.001) than those travelling less than 50 km. The overall survival for these patients was also better (82.4% vs 75.7%, p= 0.002) compared to patients travelling less than 50 km. Conclusion: The distance to a hospital dictates a patient's access to continuity of care through adjuvant chemoradiotherapy and regular follow-ups. Less than half of brain tumour patients in Pakistan had access to brain tumour surgery care within 50 km of their homes. Overall outcomes were significantly better in patients travelling more than 50km for neurosurgical care - suggesting a distance bias effect. Keywords: Distance travelled, Health disparities, Neuro-oncology, LMIC, Cancer epidemiology. Continue...